Self-efficacy as a Mediator in the Relationship between Self-esteem and Social Conformity in Emerging Adulthood - Mary, Jane; Tan, Delbert Amadeus; Nainggolan, Daniel Jeremy; Sunardi, Thessalonica Chantalie Kirsten; Riasnugrahani, Missiliana (Universitas Medan Area, 2025)
This study aimed to investigate the relationship between self-esteem and social conformity with self-efficacy posited as a potential mediator among emerging adults. As emerging adults, one of the critical developmental tasks is the consolidation of personal identity. In this identity formation process, which include significant influences from the environment, made emerging adults particularly prone to social conformity pressures. The quality of self-esteem and self-efficacy is presumed to directly impact the degree of social conformity observed in this population. Data collection was executed via a questionnaire employing convenience sampling, yielding responses from 320 undergraduate students at Bandung City. Mediation analysis using Hayes' Process Model 4 revealed a significant association between self-esteem and social conformity; however, no significant mediating effect of self-efficacy was found between self-esteem and social conformity. Notably, self-esteem was also found to be significantly correlated with self-efficacy. This finding shows that self-esteem has a great importance for emerging adults. This is due to its significant correlation to both social conformity and self-efficacy.